The rise of the democracy – authoritarianism cleavage and opposition coordination in Turkey (2014–2019). Issue 8 (16th November 2020) - Selçuk, Orçun; Hekimci, Dilara
ABSTRACT: This article examines the coordination of opposition parties in Turkey between the 2014 presidential and the 2019 local elections. To explain opposition coordination from secular, Turkish nationalist, pro-Kurdish, and Islamist parties, the article points out a rising democracy-authoritarianism cleavage. As Turkey became one of the most pronounced cases of democratic backsliding worldwide, this political cleavage gradually overshadowed historically rooted social cleavages and incentivized the opposition parties to coordinate in the name of fighting for democracy. The article shows that in seven electoral contests, the opposition parties coordinated in the form of nominating joint candidates, encouraging strategic voting, running a unified campaign, helping presidential candidates collect signatures, promising to support each other in the runoff, pledging to form a transitional government, transferring deputies to be on the ballot, nominating members of the smaller opposition parties under a larger party's list, not competing in certain districts against each other, and establishing an official alliance. Thanks to their extensive menu of coordination, the opposition parties challenged the ruling party's predominance, undermined its parliamentary majorities, and won local elections in key cities. The article's causal argument and findings have implications for opposition coordination in authoritarian regimes.